Western dominance in international relations? the internationalisation of IR in Brazil and India - Alejandro, Audrey (Worlding beyond the West, 2019)
Since the 1970s, a 'critical' movement has been developing in the humanities and social sciences denouncing the existence of a 'Western dominance' over the worldwide production and circulation of knowledge. However, thirty years after the emergence of this promising agenda in International Relations (IR), this discipline has not experienced a major shift